Cellular impact and biodegradability of S- and N-doped graphene quantum dots on human monocytes and macrophages - Song, Zhengmei (2024)
Graphene quantum dots (GQDs), small graphene domains with lateral dimensions lower than 10 nm, are increasingly used in electronics, composites, and biomedicine. Chemical doping of GQDs allows tuning their optical properties. Immune cells are among the first cells exposed to nanomaterials entering a living body, rapidly triggering a downstream immune response. However, the assessment of the impact of chemically-doped GQDs on the immune system remains rather limited if not absent. In this context, the effects and the biodegradability of sulfur-doped and nitrogen-doped GQDs (S-GQDs and N-GQDs) on human monocytes and macrophages are evaluated. The metabolic activity, membrane integrity, apoptosis, and intracellular reactive oxygen species (ROS) generation are studied. In parallel, the degradation of GQDs using human myeloperoxidase and a peroxynitrite-mediated system is investigated in test tube. Their degradation in macrophages is also pursued. High-resolution transmission electron microscopy (HRTEM), fluorescence spectroscopy, Raman, and flow cytometry are used to confirm the degradation. Overall, both GQDs exert little activation on monocytes and macrophages although they decrease the metabolic viability in a dose-dependent manner. The loss of native GQD structure and crystal lattice provide evidence of their biodegradability. Both the safety and biodegradability of S-GQDs and N-GQDs ensure their potential in biomedical applications.